Edukasi Pemanfaatan Teknologi Teropong Untuk Pengamatan Benda Langit Bagi Warga SDIT Tahfidzul Qur’an Mutiara Insan Sukoharjo - Widiyatmoko, Wahyu; Wibowo, Yunus Aris; Dewi, Ratih Puspita; Santoso, Dimas; Rahmadi, Alwi Dwi; Taufiqurrahman, Alwi (Abdi Geomedisains, 2024)
SDIT Tahfidzul Qur'an Mutiara Insan Sukoharjo is an Islamic school that aims to correlate science with the Qur'an. One approach is through observing celestial objects, but the school currently lacks a telescope to provide students with hands-on experience. This community service program aims to educate participants about space using Stellarium simulation software and direct observation of celestial objects with a telescope. The program was carried out in three stages: preparation, implementation, and evaluation. The activities were attended by 9 teachers and 120 students. The program included educational sessions on utilizing telescopes for celestial observation, which successfully increased participants' enthusiasm for learning about celestial objects. The use of Stellarium software provided participants with a new experience by simulating various functions to display visualizations of celestial phenomena. Telescope-based observation also became a novel experience, with many participants eager to try observing through the telescope. The high level of enthusiasm among participants indicates that similar activities should be conducted regularly to boost motivation in learning about celestial objects.